A case of peripancreatic plexiform schwannoma - Kenji Fukushima; Makoto Shinzeki; Kentaro Tai; Masaki Omori; Natsuko Yamauchi; Tomoko Tanaka; Yasunori Matsuda; Hiroshi Ashitani; Kenichi Tanaka (Surgical Case Reports, 2021)
Abstract Background Plexiform schwannoma is one of the least common variants of schwannoma, accounting for only 5% of all schwannoma cases. It generally occurs in the skin and subcutaneous tissues and is uncommon in deep soft tissue or viscera. We present an extremely rare case of plexiform schwannoma arising from the peripancreatic plexus. Case presentation A 29-year-old man presented with hyperglycemia detected during a medical checkup. He was diagnosed with type 1 diabetes based on the clinical findings and laboratory tests. During the diagnostic process for diabetes, a 2.5 cm mass was incidentally detected in the pancreas by abdominal ultrasound. Contrast-enhanced computed tomography revealed a mass that was gradually enhanced at the body and tail of the pancreas. Magnetic resonance imaging revealed low signal intensity of the mass on T1-weighted images and high signal intensity on T2-weighted and diffusion-weighted images. Magnetic resonance cholangiopancreatography showed no abnormal findings in the main pancreatic duct. Endoscopic ultrasonography (EUS) showed a lobulated, low-echoic mass with a clear boundary. EUS-guided fine needle biopsy was performed, and spindle-shaped cells that were diffusely immunopositive for S-100 and negative for c-kit and desmin were detected, resulting in a diagnosis of a neurogenic tumor arising from the pancreas or the peripancreatic nerve plexus. The patient underwent laparoscopic spleen-preserving distal pancreatectomy. Although the tumor was connected to the splenic plexus, the splenic artery could be divided along its adventitial plane. Macroscopic findings of the excised tumor consisted of multiple yellowish-white nodules, and its histopathological features were consistent with plexiform schwannoma. There was no pancreatic tissue on the dorsal surface of the tumor, which suggested that the tumor arose from the peripancreatic nerve plexus. Conclusions The findings documented herein can aid in the differential diagnosis of peripancreatic schwannoma and in planning appropriate treatment.